Plakaty filmowe Mieczysława Górowskiego w kontekście twórczości artysty - Górowska, Katarzyna (Załącznik Kulturoznawczy, 2024)
The content of this article is based on the research carried out for the resulting dissertation on the work of Mieczysław Górowski (doctoral thesis defended at the Institute of Art Sciences, Faculty of Humanities, John Paul II Catholic University of Lublin). The article refers to a small section of the artist’s oeuvre, namely film posters. It should be emphasized that the following article is the first study of Mieczysław Górowski’s film posters. While preparing to write both my doctoral thesis and the present article, I have carefully read widely available academic publications, which are few in number and selectively related mainly to the artist's poster art, as well as articles published in professional magazines on art and design or in the daily press and exhibition catalogues. What gave me the opportunity for a new and fresh look at the artist's work, was the unlimited access to the artist's family archive, and the materials found therein were used for the first time. The article presents a brief description of Mieczysław Górowski as an artist, his technique and the area of his work, which is the poster, including film poster. The text is also supplemented by the statements concerning this art by the author himself, and the people associated with him both professionally and privately.